Shikimic acid attenuates oxidative stress-induced senescence in 3D4/21 cells by modulating PARP1 activity and DNA damage response - Mo, Kaibin; Wu, Chengyu; Wu, Weichun; Zhang, Yicheng; Yang, Linlin; Li, Li; Huang, Xianhui (Frontiers in Nutrition, 2025)
BackgroundAlveolar macrophage (AM) dysfunction driven by oxidative stress contributes significantly to human chronic lung diseases like COPD and IPF. This oxidative stress often leads to DNA damage and cellular senescence, perpetuating inflammation. Shikimic acid (SA), a natural compound with antioxidant potential, requires investigation for its specific protective mechanisms in AMs, particularly regarding DNA repair and senescence modulation, to evaluate its therapeutic relevance.MethodsPorcine AMs (3D4/21 cells) were pretreated with SA and the positive control N-Acetyl-L-cysteine, respectively, before oxidative challenge with tert-butyl hydroperoxide (TBHP). We assessed cell viability (CCK-8), cytotoxicity (LDH), oxidative stress and inflammation markers (ROS, NO, iNOS, COX-2). Transcriptomics identified global gene/pathway changes. Western blotting validated key DNA damage response (DDR) proteins (XRCC1 and PARP1) and poly (ADP-ribose) (PAR) levels (indicative of PARP1 activity). Senescence was determined via senescence-associated β-galactosidase (SA-β-gal) staining and ELISA for senescence-associated secretory phenotype (SASP) factors (TNF-α, IL-1β, IL-6, IL-8).ResultsSA pretreatment significantly enhanced cell viability, decreased LDH release (P < 0.05), and markedly reduced intracellular ROS and NO levels (P < 0.05) compared to TBHP-stressed controls. Pro-inflammatory iNOS and COX-2 expression was also significantly lowered by SA (P < 0.05). Transcriptomics revealed significant alterations in gene expression, highlighting enrichment in DNA repair and senescence pathways. Mechanistically, SA significantly counteracted the TBHP-induced upregulation of XRCC1 and PARP1 protein levels, and PAR levels (P < 0.05), suggesting normalization of the DDR. Furthermore, SA substantially decreased the percentage of senescent (SA-β-gal positive) cells (P < 0.05) and suppressed the secretion of multiple SASP factors (P < 0.05).ConclusionSA effectively restores homeostasis in oxidatively injured 3D4/21 cells by concurrently mitigating oxidative stress and inflammation, modulating the DDR, particularly PARP1 activation and associated factors, and attenuating cellular senescence. This positions SA as a promising candidate for further investigation as a therapeutic agent for human lung diseases characterized by macrophage dysfunction and oxidative pathology.